Accounting support for the analysis of enterprises marketing activities efficiency (Economics and region, 2024)
The aim of the article is determination of features of accounting and analytical supports for the effectiveness of enterprises marketing activities evaluating. The specified goal was achieved through specification and scientific substantiation of aspects of the display of economic processes of the implementation of marketing activities in the accounting system, based on the need for optimal application of the analytical function of the management system. The functioning of marketing activity segments is accompanied by the implementation of a certain set of business operations. Their сontent consists the implementation by the responsible persons of a complex set of measures, as a result of which the enterprise uses its resources, receives income related to this volume, and, as a result, changes occur in the volume and structure of the sources of its assets and their formation (equity and liabilities). At the same time, segments of marketing activity are characterized by the use of various types of resources, their volume and structure, which affects the current values of the parameters of economic operations, as well as their effectiveness.To perform the procedures for analyzing the effectiveness of marketing activities, it is necessary to define a system of relevant indicators. The basis of such a system should be the interests of information users, on the basis of which various types of decisions are made to ensure the achievement of strategic, tactical and operational goals of the enterprise as a whole. Such indicators can include the amount of costs associated with the implementation of business operations in the context of the marketing activities. The indicator can be used for the purpose of analyzing of marketing activities as a parameter whose value is determined for a certain reporting period, as well as for characterizing the dynamics of processes occurring over a long period of time. The system of indicators that can be used for the purposes of analyzing the effectiveness of the marketing activity of the enterprise should also include the amount of income associated with the stated costs. This concerns the amount of the enterprise's income from operational activities, since its marketing component is one of the leading factors in the formation of financial results.In addition to the value (absolute) indicators characterizing the volume of costs and revenues of the enterprise related to marketing activities, in order to perform measures to analyze its effectiveness, indicators of the ratio of costs and related revenues should be used, namely, indicators of cost intensity and cost return of marketing activity. Indicators that do not have value characteristics can also be used to evaluate the effectiveness of marketing activities of enterprises. These indicators can be used, mainly, to determine the effectiveness of the company's marketing activities from the point of view of evaluating its position on the sales markets, as well as to analyze the effectiveness of the personnel involved in the planning and implementation of the relevant processes. Another group of indicators that can be used to achieve the goals of analyzing the effectiveness of the marketing activity of the enterprise characterizes the ratio of changes that occur in the results of functioning and in the resources used for this. In this context, we are talking about the use of incremental analysis and marginal analysis methods. These indicators ensure the selection and application of analytical procedures in relation to the accounting segments of marketing activity, which include the segments of customer search, order processing, sales and settlements. Data that can be used to formalize these indicators can be obtained from primary accounting documents, accounting registers, as well as forms of financial, management fiscal, statistical and other types of reporting. So, analytical assessment of the effectiveness of the enterprise's marketing activity is determined based on the application of a system of value and natural indicators, formalized in absolute, relative and dynamic values. Such values can be obtained from various sources, which are diverse in terms of data formalization methods, used information carriers, as well as the level of trust on the part of users. The subject of further research may be the aspects of the choice by subjects performing analytical measures of algorithms for determining the importance of individual indicators and their groups, based on the tasks of the subjects of the management system of the levels of individual economic operations, segments of activity, responsible persons, functional and structural divisions of the enterprise etc.
Keywords: marketing activities; efficiency; analysis; accounting; analytical indicators